Desempenho agronômico e eficiência de utilização de fósforo por cultivares de milho - Almeida, Antônio Fabrício de (2019)
Corn (Zea mays L.) is the most cultivated cereal in the world. However, some factors contribute for agricultural failure in the Northeast region, standing out the choice of cultivars, which generally present different responses to the use of phosphorus. Thus, the present research had as objective to evaluate the agronomic performance and the efficiency of the use of phosphorus by corn cultivars for the production of green and grain ears. Two experiments were conducted, one in the rainy season (March to June) and the other in the dry period (August to December), both at the Rafael Fernandes Experimental Farm, located in the community of Alagoinha, belonging to the Federal Rural Semi-Arid University, in the municipality of Mossoró - RN. A randomized complete block design was used in a 3 x 8 factorial scheme, with four replications. The treatments consisted of a combination involving three phosphorus levels (low, medium and high) and eight corn cultivars (Dona Josélia, Carrapateira, Pontinha, Cruzeta, Potiguar, BRS 2022, Status, AG 1051). Each experimental plot consisted of three rows of 3 m in length, spaced at 0.8 m apart, containing 10 plants in each row, the central row for green maize being considered as the useful area and the right side for corn grain; both discarding a plant at each end. The evaluated characteristics were: plant height and stem insertion, stalk diameter, dry matter, plant contents and phosphorus accumulations, number and total mass of green spikes, number and mass of marketable green bean, stuffed and shredded, productivity of dry grains, agronomic, physiological, spike / grain yield, phosphorus recovery and utilization efficiencies. The cultivars showed higher productive performance when fertilized with phosphorus. The cultivars Cruzeta, Potiguar, BRS 2022, Status and AG 1051 were the best for the production of green maize. AG 1051, Pontinha and Status were the best for the production of corn grain. The cultivar Carrapateira was the most efficient in the use of phosphorus to produce green maize. The cultivars Dona Josélia and BRS 2022 were the most efficient in the use of phosphorus for grain production